PENGARUH NILAI TUKAR (KURS) USD/IDR, TINGKAT SUKU BUNGA SBI, INFLASI DAN JUMLAH UANG YANG BEREDAR (M2) TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) - DEWI KUMALASARI (Jurnal Akademika, 2016)
This study aims to see the development of the Indonesian capital market, one indicator thatis often used is the Composite Stock Price Index (CSPI), which is one of the stock marketindex used by the Indonesian Stock Exchange (BEI).The analytical tool used in thisresearch is multiple linear regression Composite Stock Price Index (JCI) as the dependentvariable and four independent variables, the variable rate (rate) USD / IDR, SBI interestrate, inflation and the money supply (M2 ).Based on the results SPSS calculations obtainedFcount F = 47.313 with a significance of 0.000. By using a significance level of 0.05 wasobtained value of F table 3,06. Then Fcount (47.313)> F table (3.06), or the significance ofF 0,000 showed less than 0.05 so it can be concluded that the four independent variables arethe exchange rate (exchange rate) USD / IDR, SBI interest rate, inflation and the moneysupply (M2) jointly affect the Composite Stock Price Index (CSPI) in Indonesia StockExchange (BEI). Partial variable rate (rate) USD / IDR and the money supply (M2)significantly. While the variable interest rate of SBI and inflation is not significant. And ofthe four variables of the most dominant influence on Composite Stock Price Index in theIndonesia Stock Exchange (BEI) is the exchange rate (exchange rate) USD / IDR. Withtcount of -3.433 and significance probability of 0.004.Keywords: JCI, Exchange Rates, Interest Rates, Inflation, Money Supply